Research on the Awareness and Application of Strategic Management Accounting Instruments in Lithuanian Companies - Medeckytė, Kamilė; Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2021)
In recent decades, as the newly created internal and external environment conditions have radically changed the environment of business, the process of creating and implementing business strategy became more relevant. The data, generated by strategic management accounting, makes this process more efficient. The article examines the concept of the strategic management, its importance and related instruments. The article provides results of the research carried out to determine the level of awareness and application of strategic management accounting instruments in Lithuanian companies. Empirical research has shown that the level of awareness and application of the strategic management accounting instruments in Lithuanian companies is minor. The most common strategic management accounting instruments are as follows: customer profitability analysis, benchmarking, competitive position monitoring, strategic pricing, and strategic costing. The least known and, according to the research, the least applicable strategic management accounting instruments are: attribute costing, product life cycle accounting and brand value budgeting. According to the study, the most significant reason for the difficulties in implementing strategic management accounting instruments is the lack of time required to implement the instruments.
Keywords: strategic management accounting; strategic management accounting instruments; Lithuanian companies